Compositional Variation in Trans-Ferulic, p-coumaric, and Diferulic Acids Levels Among Kernels of Modern and Traditional Maize (Zea mays L.) Hybrids - Zavala-López, Mariana; Flint-García, Sherry; García-Lara, Silverio (Frontiers in Nutrition, 2020)
Maize is one of the most heterogenous cereals worldwide in terms of yield, physical characteristics, and biochemical composition due to its natural diversity. Nowadays the use of maize hybrids is extensive, while the use of landraces is mostly local. Both have become an important genetic resource useful to identify or generate varieties with desirable characteristics to overcome challenges of agronomic performance, nutritional quality, and functionality. In terms of functionality, one of the most studied families of compounds are phenolic acids. These compounds have been associated with the improvement of human health because of their antioxidant capacity. To evaluate the diversity of phenolic compounds in maize, two collections, the Nested Association Mapping (NAM) founders and 24 landraces, were crossed with B73. Phenolic compounds were extracted and quantified by HPLC-PDA. Soluble and cell wall phenolic acids were identified and significant differences between and within the NAM and Landrace collections were assessed. Soluble p-coumaric acid quantification of B73 x NAM hybrids presented high variation as the range went from 14.45 µg/ g dw to 132.34 µg/ g dw. In the case of B73 x Landrace hybrids, wide variation was also found, ranging 25.77 to 120.80 µg/g dw. For trans-ferulic acid, significant variation was found in both hybrid groups: B73 x NAM presented an average of 157.44 µg/g dw whereas the B73 x Landrace hybrids average was 138.02 µg/g dw. In cell wall p-coumaric acid, a range from 30.93 to 83.69 µg/g dw and 45.06 to 94.98 µg/g was found for landrace and NAM hybrids, respectively. For cell wall trans-ferulic acid, a range from 1641.47 to 2737.38 µg/g dw and 826.07 to 2536.40 µg/g dw was observed for landrace and NAM hybrids, respectively. Significant differences between hybrid groups were found in p-coumaric acid, for both soluble and cell wall-bounded. Therefore, maize hybrids produced by conventional techniques using both modern and traditional varieties showed a high diversity in terms of phenolic compounds, denoting the role of these compounds in the maize ability to endure different environment conditions. This study provides a platform of comparison through the unveiling of maize phenolic compounds for future breeding efforts.